Pengaruh E-Service Quality dan E-Trust Terhadap Kepuasan Pelanggan Pada Pengguna Aplikasi PLN Mobile Kota Padang Panjang - Luthfiani, Fatma; Yuhefizar, Yuhefizar; Josephine Sudiman (Jurusan Akuntansi Politeknik Negeri Padang, 2024)
Technology has become an inseparable part of people's daily lives. The high use of cellphones and the internet in Indonesia has triggered companies to follow the wishes of the community by creating several applications that are used for the above activities. Several mobile applications already exist in Indonesia, one of which is for payments and purchases. One of the companies that provides mobile payment applications is the State Electricity Company (PLN), which is an Indonesian State-Owned Agency that operates in the electricity sector. In the final assignment with the title